INVENTING CME IN PAKISTAN: A SWOT ANALYSIS: CME in Pakistan - Aslam, Maj Gen [Retd] Muhammad (Pakistan Armed Forces Medical Journal, 2012)
Continuing Medical Education [CME] has gained momentum over the past decade and the resistance for its adoption has been diluted all over. SWOT is an acronym for Strength Weakness, Opportunity and Threat. SWOT analysis is a method of analyzing a business [or organization], its resources and its environment. SWOT analysis is instrumental in strategy formulation and selection. It is a strong tool but it involves a great subjective element. It is best used as a guide and not as a prescription. SWOT analysis works through an internal analysis [Audit or Review] and external analysis [Audit or Review]. The internal analysis comprises Strengths and Weaknesses, whereas, the external analysis consists of Opportunities and Threats. SWOT synchronises the institution’s resources and capabilities with the competitive environment. Though, basically it was used in business and industry but is found equally useful in developing community health, health care systems, education and even personal growth. SWOT analysis helps in strategic planning by [a] increasing source of information [b] building organisation’s strength [c] reversing weaknesses [d] maximizing opportunities [e] overcoming organisation’s threats [f] identifying core competencies [g] setting of objectives for planning and in [h] knowing past, present and future to enable to make the plans for tomorrow.